2007
DOI: 10.1094/php-2007-0119-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pathogenicity of Bipolaris and Curvularia spp. on Dwarf and Ultradwarf Bermudagrasses in Florida

Abstract: Isolates of Curvularia lunata, C. geniculata, Bipolaris hawaiiensis, and B. cynodontis were tested for pathogenicity on the hybrid bermudagrass cultivars Tifdwarf, TifEagle, and FloraDwarf at 20 and 30°C. Curvularia lunata, C. geniculata, and B. hawaiiensis produced some minor leaf tip necrosis at the cut ends of leaves 24 to 48 h after inoculation. Bipolaris cynodontis produced significant tip dieback and leaf spotting on all three cultivars at both 20 and 30°C, and disease severity was higher at 20°C than at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…This indicates that MiniVerde may have increased field tolerance to both B. cynodontis and S. homoeocarpa , compared with Champion, when managed under similar conditions. To our knowledge, these UDB cultivars have not been evaluated for resistance to foliar diseases; however, another study demonstrated an increased leaf spot susceptibility of FloraDwarf compared with TifEagle and Tifdwarf cultivars (Brecht et al, 2007). Results of this study, together with previous studies, indicate that variation in disease resistance likely exists among modern UDB cultivars (Bonos et al, 2003; Brecht et al, 2007; Bonos and Weibel, 2008; Tomaso‐Peterson and Young, 2010; Steketee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that MiniVerde may have increased field tolerance to both B. cynodontis and S. homoeocarpa , compared with Champion, when managed under similar conditions. To our knowledge, these UDB cultivars have not been evaluated for resistance to foliar diseases; however, another study demonstrated an increased leaf spot susceptibility of FloraDwarf compared with TifEagle and Tifdwarf cultivars (Brecht et al, 2007). Results of this study, together with previous studies, indicate that variation in disease resistance likely exists among modern UDB cultivars (Bonos et al, 2003; Brecht et al, 2007; Bonos and Weibel, 2008; Tomaso‐Peterson and Young, 2010; Steketee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf spot, caused by Bipolaris cynodontis (Marignoni) Shoemaker, and dollar spot, caused by Sclerotinia homoeocarpa F.T. Bennett, are two diseases that affect UDB putting green turf (Couch, 1995; Taliaferro, 1995; Walsh et al, 1999; Couch, 2000; Smiley et al, 2005; Brecht et al, 2007; Andrae et al, 2009; Latin, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Until now over 100 species of Bipolaris have been described (Brecht 2005, Crous et al 2004). The present species is similar to B. spicifera in all essential features, but it differs from the type specimen of this fungus in conidial germination pattern; in our isolates conidia germinate to form swollen germ tubes from both ends and swollen germ tube undergo multiple branching soon after formation.…”
Section: Discussionmentioning
confidence: 99%